PERANCANGAN JARINGAN KOMUNIKASI SISTEM INFORMASI DAN ADMINISTRASI BRIMOB (SIAB) BERBASIS SERAT OPTIK - Ariman .; Mochamad Iklil (Institut Sains dan Teknologi Nasional, 2021)
Markas Komando Brimob uses optical fiber as a transmission media in the design of the Sistem Informasi dan Administrasi Brimob (SIAB) communication network. Optical fiber has a large transmission capacity, therefore fiber optic networks are implemented on network of SIAB. This facility includes withdrawal of fiber optic cable from Mako Brimob to seven points, namely Pool Mako, Mako Gegana, Pool Bengkel Gegana, Detasemen Gegana, Pool KBR, Pool Pelopor, and Danpas Pelopor. The design of the SIAB network is adjusted to the needs of the Mako Brimob such as: 10-10 of BER, 100 Mbps of data speed, and 1310 nm of wavelength. The optical equipment used were single fiber optic tube loosen mode, PIN photodiode light detector, optical laser diode, and SC connector. From the power link analysis, the maximum distance without using an optical amplifier was 491.9 km. Then, the maximum speed was 896 Mbps measured using rise time budget. Keywords: Power link budget, Rise time budget